Oncology Communication Skills Training: Bringing Science to the Art of Delivering Bad News - Stovall, Mady C. (J Adv Pract Oncol, 2015)
Review of "Effect of communication skills training program for oncologists based on patient preferences for communication when receiving bad news: A randomized controlled trial" by Fujimori et al. (2014), Journal of Clinical Oncology, 32, 2166–2172. For a further discussion of survey research, please see the related article by Julie Ponto starting on page 168.